Does organized sport participation during youth predict healthy habits in adulthood? A 28‐year longitudinal study. (16th May 2018) - Palomäki, S.; Hirvensalo, M.; Smith, K.; Raitakari, O.; Männistö, S.; Hutri‐Kähönen, N.; Tammelin, T.
Abstract : Health behaviors in youth can predict the same behaviors later in life, but the role of sport participation in predicting healthy lifestyle habits is unclear. This study aimed to investigate the association between participation in organized youth sport and adult healthy lifestyle habits. Data from the longitudinal Cardiovascular Risk in Young Finns Study (YFS) with a 28‐year follow‐up were used. The participation in sport‐club training sessions was self‐reported by 9‐18‐year‐olds in 1983 and 1986 (n = 1285). During 2011, participants (aged 37‐43‐year old) reported their smoking status, alcohol consumption, fruit and vegetable consumption, and physical activity. Odd ratios (OR) were calculated using logistic regression, to examine how participation in organized youth sport was associated with having three or four versus fewer (0‐2) healthy habits in adulthood. Participants who were active in youth sport in both 1983 and 1986 had almost two times greater odds of having three or four healthy habits in adulthood than those who were not active at both time points (OR: 1.75, 95%CI: 1.11‐2.76). When the analyses were stratified by sex, the findings were statistically significant among women (OR: 2.13, 95%Cl: 1.13‐3.99) but not men (OR: 1.27, 95%CI: 0.63‐2.58). The results suggest that participation in organized youth sport could promote healthy lifestyle choices.